Winnie-the-Pooh : The Complete Collection of Stories and Poems - Milne, A. A.; Illustrated by Shepard, E.H. (London Reed Books Children's Publishing, 1973)
This gift edition contains all four of A.A. Milne's classic children's books of verse and stories about Christopher Robin and Winnie-the-Pooh, accompanied by E.H. Shepard's original drawings and illustrations.
Include colour illustrations
Keywords: Toys -- Winnie-the-Pooh (Fictitious character) -- Teddy bears